The Existence of Jinn in the Perspectives of Mufassirin - Nur, Faisal Muhammad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Allah created the jinn, which are invisible creatures. Allah created them before humans, according to the Quran. However, the existence of jinn and demons in the physical world has always been a subject of search and attention for every intellectual group that seeks to prove their existence. The purpose of this research is to understand the understanding of the mufassirin scholars regarding the existence of jinn and demons in the physical world, as well as their attitudes towards their existence. This research utilizes a literature review method based on the classical books of the Mufassirin scholars. The results of the study indicate that (1) jinn are creatures created by Allah before humans, (2) Jinn exist in the physical world even though humans cannot observe their presence, (3) Believing in the existence of jinn in the physical world is part of having faith in the unseen, (4) Believing in the existence of jinn and demons in the physical world is by the teachings of the Quran and Sunnah.